Competing through competences (Cambridge University Press, 2002)
This book helps you to understand your organisation's capabilities and limitations. It will show you how to build a more sustainable competitive advantage by revealing the techniques that underlie your firm's strategy, and explain how to manage these resources to reinforce your strengths and ameliorate your weaknesses. Written for managers of small-medium sized businesses and industry consultants, this book also forms part of a three volume set covering business strategy, performance, and competencies. A CD included with the book provides much supporting material